Temsirolimus for advanced renal cell carcinoma. Issue 1 (January 2014) - Bergmann, Lothar; Maute, Luise; Guschmann, Michael
Abstract : Renal cell carcinomas (RCCs) represent one of the ten leading cancer entities with an increasing incidence especially in the western world. Unfortunately, about 25% of the patients develop metastatic RCC (mRCC) associated with a most unfavorable prognosis. In the recent years, various new agents targeting VEGF or VEGF receptor (VEGFR) or the mTOR pathway have been approved for the treatment of mRCC with significant prolongation of progression-free survival and, in part, of overall survival (OS). Targeting the mTOR kinase is an interesting option for mRCC. Temsirolimus, one of the available mTOR inhibitors, has been approved as a single agent in poor-risk mRCC patients based on the pivotal Phase III trial showing a significant superiority in OS versus IFN-α or temsirolimus + IFN-α, which has been verified by a pivotal Phase III trial. The benefit has been shown for clear cell carcinoma and papillary RCC as well. For poor prognosis patients, temsirolimus improves median survival by 3.6 months. In second-line treatment compared with sorafenib following first-line treatment with sunitinib temsirolimus showed a relative progression-free survival benefit for patients with nonclear cell RCC with temsirolimus. The median OS for the temsirolimus group was 12.27 and 16.64 months for the sorafenib group. In 2007, the US FDA granted approval for temsirolimus for the treatment of advanced RCC.